Uremic pruritus - Mettang, Thomas; Kremer, Andreas (Kidney International, 2015)
Uremic pruritus or chronic kidney disease-associated pruritus (CKD-aP) remains a frequent and compromising symptom in patients with advanced or end-stage renal disease, strongly reducing the patient's quality of life. More than 40% of patients undergoing hemodialysis suffer from chronic pruritus; half of them complain about generalized pruritus. The pathogenesis of CKD-aP remains obscure. Parathormone and histamine as well as calcium and magnesium salts have been suspected as pathogenetic factors. Newer hypotheses are focusing on opioid-receptor derangements and microinflammation as possible causes of CKD-aP, although until now this could not be proven. Pruritus may be extremely difficult to control, as therapeutic options are limited. The most consequential approaches to treatment are: topical treatment with or without anti-inflammatory compounds or systemic treatment with (a) gabapentin, (b) ?-opioid receptor antagonists and ?-agonists, (c) drugs with an anti-inflammatory action, (d) phototherapy, or (e) acupuncture. A stepwise approach is suggested starting with emollients and gabapentin or phototherapy as first-line treatments. In refractory cases, more experimental options as ?-opioid-receptor-antagonists (i.e., naltrexone) or ?-opioid-receptor agonist (nalfurafine) may be chosen. In desperate cases, patients suitable for transplantation might be set on 'high urgency'-status, as successful kidney transplantation will relieve patients from CKD-aP.
EVALuna2:1996